POTTERY VESSELS IN CENTRAL ASIA FROM THE HISTORY OF EMERGENCE - Rahmanov Zainabuddin (Zeta Repository, 2023)
The article analyzes the emergence and development of pottery in Central Asia. In it, the author focused on the role of pottery in the history of mankind, the methods of pottery making, the decorations on pottery in the Central Asian region, and the archaeological classification of the images on it.